A new species of Oscarella (Demospongiae: Plakinidae) from the Western Sea of Japan - Ereskovsky, Alexander V. (Zootaxa, 2006)
Oscarella malakhovi sp. nov. is described from the waters of Peter the Great Bay (northwestern Sea of Japan, Russia) at depths between 0.4–4 m from a rocky coast. This is the first record of the genus Oscarella from the North-Western Pacific. The new species is characterized by its pinky-beige to yellow color, undulating appearance, lumpy, microlobate surface, soft, slimy consistency, two particular kinds of cells with inclusions (vacuolar and granular cells), and of two kinds of endobiont bacteria. The new species of Oscarella is clearly different in cell, endobiotic bacteria content, and external morphology from all previously described species of Oscarella.